Investigation of qualitative indicators of non-tobacco nicotine-containing shisha mixtures: consumer characteristics and nicotine content - M. V. Shkidyuk; S. V. Gvozdetskaya (Новые технологии)
Shisha tobacco and non-tobacco nicotine-containing shisha mixtures are an alternative way of consuming nicotine with a potential reduction in toxicological risk apart from smoking cigarettes. The Federal Law of July 31, 2020 N 303-FZ «On Amendments to Certain Legislative Acts of the Russian Federation on the Protection of Citizens’ Health from the Consequences of Consuming Nicotine-Containing Products» [1] equated the consumption of nicotine-containing products with the traditional use of tobacco. The absence of state regulation predetermines the relevance of conducting large-scale studies of both shisha tobacco and non-tobacco nicotine-containing shisha mixtures. The specificity of the product consumption in this segment is the production of a highly dispersed aerosol that occurs without the combustion / smoldering process. The variety of the ingredient composition of nicotine-containing shisha mixtures determines the consumer properties and the toxic load of the aerosol produced. Assessment of the toxic effects of an aerosol should take into account the concentration of the ingredients in the mixture, the nicotine content and their transfer to the aerosol. The methods for determining the composition of nicotine-containing products have been updated in the laboratory of technology for the production of tobacco products of the FSBSI RSRITTP [2] over the past years. The article presents the results of studies to determine the content of glycerin and propyl- ene glycol, which determine the consumer properties of the product and nicotine as the main factor that determines the potential level of toxic risk of the product in shisha tobacco and non-tobacco nicotine-containing shisha mixture. The result of the research: the dependence of the tasting assessment on the content of VG glycerin in the ingredient composition of the mixture has been revealed. Insufficient glycerin content is the reason for the weak ability to form a saturated dense aerosol. The content of nicotine in the studied samples of shisha mixture has been determined and transition of nicotine into aerosol has been established.